Communication Strategy Of Radio Republik Indonesia (RRI) Bengkulu In Retaining Listeners Through Youtube Content (A Study On Programa 1 Channel: Dialog Interaktif Pagi) - Tinton Irawan; Sri Narti; Martha Heriniazwi Dianthi (Universitas Dehasen Bengkulu, 2026)
This study examines the communication strategy of Radio Republik Indonesia (RRI) Bengkulu in retaining listeners through YouTube content, focusing on Programa 1’s “Dialog Interaktif Pagi.” The research uses a descriptive qualitative approach to capture how a public broadcasting institution adapts to digital media consumption. Data were collected through observation, in-depth interviews with key informants (the Head of the Broadcasting Team and the program host), and documentation of broadcasting activities and YouTube content. The analysis is guided by Susan Tyler Eastman’s framework, which highlights five strategic dimensions: compatibility, habit formation, control of audience flow, conservation of program resources, and mass appeal. Findings indicate that RRI Bengkulu aligns program topics and presentation styles with audience needs, maintains listening habits through consistent scheduling and recognizable program identity, and directs audience flow by integrating on-air and online promotion. The station also optimizes limited resources by repackaging broadcast materials into digital formats and strengthening teamwork in production planning. Finally, RRI Bengkulu enhances mass appeal by selecting accessible themes, encouraging audience participation, and using YouTube to expand reach beyond traditional radio listeners. Overall, these strategies help RRI Bengkulu sustain loyal audiences while attracting new viewers in the digital era, supporting the relevance and competitiveness of public radio broadcasting.